YAP maintains the production of intermediate progenitor cells and upper‐layer projection neurons in the mouse cerebral cortex. Issue 5 (28th December 2021) - Su, Yi‐Ching; Hung, Tzu‐Heng; Wang, Tzu‐Fang; Lee, Ying‐Hsuan; Wang, Tsu‐Wei; Yu, Jenn‐Yah
Abstract: Background: The Hippo pathway is conserved through evolution and plays critical roles in development, tissue homeostasis and tumorigenesis. Yes‐associated protein (YAP) is a transcriptional coactivator downstream of the Hippo pathway. Previous studies have demonstrated that activation of YAP promotes proliferation in the developing brain. Whether YAP is required for the production of neural progenitor cells or neurons in vivo remains unclear. Results: We demonstrated that SATB homeobox 2 (SATB2)‐positive projection neurons (PNs) in upper layers, but not T‐box brain transcription factor 1‐positive and Coup‐TF interacting protein 2‐positive PNs in deep layers, were decreased in the neonatal cerebral cortex of Yap conditional knockout (cKO) mice driven by Nestin‐Cre . Cell proliferation was reduced in the developing cerebral cortex of Yap ‐cKO. SATB2‐positive PNs are largely generated from intermediate progenitor cells (IPCs), which are derived from radial glial cells (RGCs) during cortical development. Among these progenitor cells, IPCs but not RGCs were decreased in Yap ‐cKO. We further demonstrated that cell cycle re‐entry was reduced in progenitor cells of Yap ‐cKO, suggesting that fewer IPCs were generated in Yap ‐cKO. Conclusion: YAP is required for the production of IPCs and upper‐layer SATB2‐positive PNs during development of the cerebral cortex in mice. Key Findings: Upper‐layer but not deep‐layer projection neurons are decreased in the cerebral cortex of brain‐specific Yap‐cKO. Cell proliferation and cell cycle re‐entry are decreased in the developing cerebral cortex of Yap‐cKO. Intermediate progenitors but not radial glial cells are decreased in the developing cerebral cortex of Yap‐cKO.